2013
DOI: 10.1371/journal.pone.0079010
|View full text |Cite
|
Sign up to set email alerts
|

Is the Improvement of CF Patients, Hospitalized for Pulmonary Exacerbation, Correlated to a Decrease in Bacterial Load?

Abstract: BackgroundCystic Fibrosis (CF) patients are vulnerable to airway colonization with Pseudomonas aeruginosa. In case eradication fails after antibiotic treatment, patients become chronically colonized with P. aeruginosa, with recurrent pulmonary exacerbation, for which patients typically are hospitalized for 2 weeks and receive intravenous antibiotic treatment. Normally, improvement of the patients' health is established.AimDetermination of the correspondence between patient improvement and changes of the P. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
(29 reference statements)
4
39
0
Order By: Relevance
“…Some studies find little change (Fodor et al, 2012;Deschaght et al, 2013;Price et al, 2013), while others are finding fluctuations in anaerobic microbial abundance (Carmody et al, 2013;Deschaght et al, 2013;Twomey et al, 2013;Zemanick et al, 2013). The WinCF system demonstrated that obligate anaerobes are abundant prior to exacerbation and actively fermenting.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies find little change (Fodor et al, 2012;Deschaght et al, 2013;Price et al, 2013), while others are finding fluctuations in anaerobic microbial abundance (Carmody et al, 2013;Deschaght et al, 2013;Twomey et al, 2013;Zemanick et al, 2013). The WinCF system demonstrated that obligate anaerobes are abundant prior to exacerbation and actively fermenting.…”
Section: Resultsmentioning
confidence: 99%
“…2007/503). Study was performed in accordance with approved national and international guidelines; written informed consent was obtained from all the patients > 18 years or from the parents and children older than 12 years, as previously reported [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…aeruginosa [1], and received the same antimicrobial treatment: Tazocin ® (Piperacillin/Tazobactam 4000mg/500mg) by intravenous administration during 15 days. Sputum samples were collected as previously reported [16,17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of research groups have studied the microbiota changes that occur around exacerbations. 61, 62 The use of antibiotics is associated with mortality benefits when treating severe exacerbations in both CF and COPD, however their use would seemingly disrupt a healthy diversity in the lower lung fields. This question has been addressed by Price and others who tracked CF patients during treatment of an exacerbation and monitored the relative amounts of individual species and the change in diversity over the course of a single exacerbation.…”
Section: The Lower Airways As An Ecosystemmentioning
confidence: 99%